Rent management and policy learning in green technology development: the case of solar energy in India - Tilman Altenburg; Tobias Engelmeier (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
To avoid irreversible damage to global ecosystems, new “green” technologies are needed. Some of those are still far from commercial maturity. In such cases, governments may create temporary rents to make investments “artificially” attractive. The creation of such rents, however, involves risks of misallocation and political capture. This article looks at rent management in the case of India's National Solar Mission. So far, the mission has been remarkably effective in triggering solar investments and keeping the necessary subsidies manageable through a process of competitive reverse bidding for tariffs. Moreover, policy design and implementation showed a good deal of experimentation and learning. Some risks remain, especially regarding the enforceability of renewable energy quotas at the level of Indian states. On the whole, however, first experiences indicate that “green rents” have been managed in a fairly effective way. Tobias Engelmeier is Managing Director of BRIDGE TO INDIA Pvt. Ltd. (http://www.bridgetoindia.com/), a consultancy focused on the Indian solar market.
Keywords: 330; Energie; Governance; Klimawandel